Jerusalem, Israel/Palästina: Die Grabung auf dem Zionshügel im Südwesten der Altstadt Jerusalems (im Bereich des historischen Anglikanisch-Preußischen Friedhofs) - Vieweger, Dieter (e-Forschungsberichte des DAI, 2023)
In the past, two archaeological campaigns of research work have been done on the Mt. of Zion. In 1894 the British Archaeologists F. Bliss and A. Dickie searched for the Byzantine City Wall and found a gate. From 1977 to 1988 the monk Bargil Pixner damaged the area massively by digging there to prove his ideas about the area: His theories have relied on the interpretation of the Gate as ‘Essene Gate’ and the presence of several Miqwaot in the wider area which in his opinion showed the habits of the Essene Community. Aside from his articles no comprehensive digging report exists. Not even the archives – neither in the archive of the IAA nor in the archive of the Dormition Abbey where Bargil Pixner lived – document a lot of additional archaeological evidence. The preliminary season of archaeological work of the GPIA in 2015 was necessary to set the site into a state that allows proper archaeological documentation and further academic treatment and research. Since the area includes multiple city walls from different periods and several gate-contexts, a proper documentation of the site provides important information for the further research on the history of the City of Jerusalem.